2022
DOI: 10.3389/fendo.2022.930271
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma D-dimer levels may be a promising indicator for diabetic peripheral neuropathy in type 2 diabetes

Abstract: BackgroundIncreased plasma D-dimer levels have been reported to be associated with a range of adverse health outcomes. This study aimed to determine whether plasma D-dimer is connected to diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes (T2D).MethodsThis study was part of a series exploring the potential risks for DPN. All patients were questioned for neurologic symptoms, examined for neurologic signs, and received nerve conduction studies to collect nerve action potential onset latency, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…D-Dimer has not been investigated extensively. However, previous work of ours has shown a relationship between diabetes progression in the presence of macrovascular disease and more recently D-dimer has been shown to be a promising marker for peripheral neuropathy 61,62 . GSSG is a sensitive oxidative stress marker, which reflects possible decreasing synthesis of GSH and increased irreversible utilization by reactive oxygen species reactions 42 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…D-Dimer has not been investigated extensively. However, previous work of ours has shown a relationship between diabetes progression in the presence of macrovascular disease and more recently D-dimer has been shown to be a promising marker for peripheral neuropathy 61,62 . GSSG is a sensitive oxidative stress marker, which reflects possible decreasing synthesis of GSH and increased irreversible utilization by reactive oxygen species reactions 42 .…”
Section: Discussionmentioning
confidence: 71%
“…The current study extends our understanding of the role of C5a as direct associations of this biomarker was observed with disease progression and presence of comorbidities, providing a useful timeline in terms of the biochemical milieu changes associated with disease progression. D-dimer has previously been reported to be already elevated in prediabetes and diabetic peripheral neuropathy has recently been associated with increased levels of D-dimer alongside fluctuations in HbA1c 61,86 .…”
Section: Diabetes Progression With Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show there is a relationship between D-dimer levels and MPV, indicating that in type 2 diabetes patients, increased platelet activation can reflect increased fibrinolytic activity [ 41 , 42 ]. D-dimers are small protein fragments produced during fibrinolysis and are well-established markers of venous thrombosis formation in the general population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show there is a relationship between D-dimer levels and MPV, indicating that in type 2 diabetes patients, increased platelet activation can reflect increased fibrinolytic activity [ 41 , 42 ]. D-dimers are small protein fragments produced during fibrinolysis and are well-established markers of venous thrombosis formation in the general population [ 42 ]. Previous studies indicated that increased D-dimer concentration was found in individuals with prediabetes [ 43 ], type 2 diabetes patients [ 42 ], or even first-degree relatives of type 2 diabetes patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%